EDUCATING CHILDREN IN THE TWENTY-FIRST CENTURY: AN INSIGHT FROM MUSLIM FAMILIES - Mahmud, Salami; Habiburrahim, Habiburrahim; ZA, Tabrani; Muchlinarwati, Muchlinarwati; Fadli, Fatmawati (Islam Futura, 2024)
Educating children in the 21st century is different from it was in the 20st century. Parents in this era face challenges because it is impossible for their children to be away from the Internet and social media. Children become asocial because of their addiction to gadgets and the Internet. However, from the Internet, they may learn different new things that allow them to get information faster than their parents do. Parents must certainly adapt to this change in educating their children so that they are not distracted by the negative effects of incorrect education caused by technological advancements. The purpose of this study is to promote some of the important knowledge that parents must have to educate their children in this century, aside from religious knowledge, as the primary foundation of upbringing in Muslim families. This research undertakes a thorough examination of scholarly work on Islamic education for children and contemporary studies on children's learning in the 21st century. After scrutinizing a range of literature, the researchers identified several pertinent references for this investigation. The results of this study elucidate that in order to effectively nurture their children in the contemporary era, parents are required to possess a profound understanding of Islamic principles alongside a continuous commitment to enhance their comprehension in diverse fields such as parenting techniques, information technology, psychology, and communication strategies.